2007
DOI: 10.1158/1055-9965.epi-07-0220
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Epithelial Ki-67 Index Is Related to Histology, Smoking, and Gender, but Not Lung Cancer or Chronic Obstructive Pulmonary Disease

Abstract: Purpose: To determine whether increased bronchial epithelial proliferation is associated with histology, smoking status, gender, age, chronic obstructive pulmonary disease (COPD), or lung cancer. Experimental Design: Cross-sectional study of 113 subjects undergoing white light and autofluorescence bronchoscopy: 27 never smokers; 27 current or ex-smokers with normal spirometry; 31 current or exsmokers with COPD; and 28 current, ex-, or never smokers with lung cancer. Ki-67 expresssion was determined by immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…Most recent phase II studies have chosen to evaluate the effects of intervention on premalignant lesions or inhibition of the carcinogenic progression. The current study confirms the finding that histology is less severe in former smokers [as is Ki-67 index (17)] and supports its feasibility for use as a biomarker. Endobronchial histology can be assessed by using a variety of measures, including Avg, Max, and DI, all of which improved in the current trial.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Most recent phase II studies have chosen to evaluate the effects of intervention on premalignant lesions or inhibition of the carcinogenic progression. The current study confirms the finding that histology is less severe in former smokers [as is Ki-67 index (17)] and supports its feasibility for use as a biomarker. Endobronchial histology can be assessed by using a variety of measures, including Avg, Max, and DI, all of which improved in the current trial.…”
Section: Discussionsupporting
confidence: 86%
“…All prior lung cancer chemoprevention studies proved negative, but several studies have revealed differences between current and former smokers regarding amount and extent of central airway damage (1517). Subjects with tobacco smoke exposure, chronic obstructive lung disease, and sputum cytologic atypia have rates of lung cancer greater than 1% yearly and are a high risk group in which chemoprevention may have utility (18).…”
Section: Introductionmentioning
confidence: 99%
“…Second, it takes many years before the risk of lung cancer is reduced after smoking cessation, not with standing the early decrease in proliferation (albeit not necessarily to “normal” levels) following smoking cessation (14, 15). Extended follow-up from the Lung Health Study showed that a decrease in lung cancer incidence was not demonstrable until 14.5 years after smoking cessation, well past the time when average Ki-67 expression has already significantly decreased according to other studies (16). Therefore, decreased Ki-67 was not mirrored by an early decrease in lung cancer risk.…”
Section: Ki-67 and Efficacy In Lung Cancer Prevention Trialsmentioning
confidence: 82%
“…Ki-67 immunostaining was conducted on tumors from treprostinil treated and control animals as as previously described(22, 23). In brief, 5 micron lung sections from the urethane, ET, and LT groups were deparaffinized, peroxidases blocked with 3% hydrogen peroxide, and antigen retrieval performed in boiling Diva Decloaker (Biocare Medical, DV2004G1) reagent under pressure for 10 min.…”
Section: Methodsmentioning
confidence: 99%